Restorative perceptions of migratory elderly: insights for inclusive urban park design in china - Chen, Yurui; Abdul Shukor, Shureen Faris; Maulan, Suhardi; Muthuveeran, Adam Aruldewan S. (Frontiers in Psychology, 2025)
IntroductionMigratory elderly—older adults who relocate to urban areas to live with their children—constitute a growing demographic shaped by global aging and rapid urbanization. Yet their restorative experiences in everyday urban nature remain under-examined. This study investigates their preferred spatial features, factors shaping restorative perceptions, and design recommendations to enhance restorative outcomes in urban parks.MethodsWe conducted semi-structured interviews with 23 migratory elderly in two parks in Chengdu, China, and applied thematic analysis.ResultsRestorative perceptions clustered around three themes: (1) personal needs; (2) place-related memory and identity; and (3) preferred spatial features. Compared with non-migrants, the migratory elderly exhibited a stronger reliance on culturally familiar cues—such as native vegetation, agrarian water features, and traditional forms—which evoked nostalgia and supported attachments to both past and present places. Although participants employed self-regulatory strategies and formed new attachments, unmet needs and usability conflicts (e.g., noise, activity clashes, and unclear wayfinding) constrained restorative benefits.Discussion and conclusionsTheoretically, extensions to restorative-environment frameworks include the introduction of migration-related discontinuities as boundary conditions, the identification of a practice- and community-mediated pathway to accelerated attachment, and the specification of a chain linking inclusive design to preferences, then to attachment, and ultimately to perceived restorativeness. Practically, we recommend a five-stage approach: (1) Planning—participatory framing to balance active and quiet zones; (2) Spatial structure—a legible hierarchy with intuitive, barrier-free links; (3) Facilities—provision of shade, seating, toilets, and lighting to balance recreation with safety and accessibility; (4) Social management—programming for solitary and group use that fosters cultural resonance; and (5) Maintenance—feedback-driven adaptation with clear wayfinding and night-time illumination. These findings underscore the value of culturally sensitive, inclusive park design in supporting psychological restoration among the migratory elderly in rapidly urbanizing societies.